Efficient tax policy ranks education higher than saving - Wolfram F. Richter (Institute for the Study of Labor (IZA), 2008)
Assuming a two-period model with endogenous choices of labour, education, and saving, it is shown to be second-best efficient not to distort the choice of education. In general this implies distorting the saving decision. Hence a strict order of policy priority is derived. Efficient tax policy ranks education higher than saving. The result assumes an isoelastic earnings function and holds else for arbitrary utility functions. Isoelasticity of earnings is justified with reference to the empirically well-founded Power Law of Learning.
urn:nbn:de:101:1-2008042187
Keywords: H21; 330; Endogenous choice of education; labour and saving; efficient taxation of human and nonhuman capital investment; power law of learning; Optimale Besteuerung; Second Best; Bildungsverhalten; Sparen; Bildungsinvestition; Investition; Lernprozess; Theorie